Comparação da razão carga/deflexão entre fios ortodônticos de Ni-Ti termoativados 0,014”x0,025” e 0,016”x0,022” - Freitas dos Reis, Paulo Henrique; Ferreira de Souza, Jose Maria; Ruella, Wagner de Sousa; Paranhos, Luiz Renato; Sakima, Mauricio Tatsuei [UNESP]; Lima-Rivera, Luciana Monti [UNESP] (Univ Federal Uberlandia, 2014)
The knowledge of the mechanical properties of nickel-titanium (NiTi) termoactives of the more accessible of the domestic market is still limited. Given this, the objective of this study was to evaluate and compare through deflection tests in brackets NiTi wires 03 term rectangular gauge 0.014 '' enabled x 0.025 '' and 0.016 '' x 0.022 '' of different brands (MORELLI (R), ORMCO (R) ORTHOSOURCE (R), ORTHOMETRIC (R), EURODONTO (R) and ADITEK (R)). All tests were carried out on universal testing machine EMIC DL 2000 under identical conditions and controlled at a temperature of 36 degrees C +/- 0.5 degrees C. Five measurements (N= 5) were performed for each thickness/wire tag that was deflected up to a limit of 4.0mm at a speed of 1.0mm/min. Each 0.2mm (round trip) of corresponding strength measured deflection for the construction of the graph of force x deflection at Tesc program version 3.04. Each graphic was evaluated according to the following variables: beginning of the Martensitic transformation (cN and mm), maximum strength (cN), the beginning and end of the plateau of deactivation (cN and mm) and length (mm) plateau. The average and standard deviation were calculated for all variables and statistical analysis was made by ANOVA tests 2 criteria and Turkey or Kruskal-Wallis and Dunn, a 5% level of significance. The results showed that the tests of 0.014 '' x0.025 '' ORTHOMETRIC (R) brands and ORMCO (R) showed the best results, as well as the wires of the MORELLI (R) and ORTHOSOURCE (R) to wires 0.016 '' x0.022 ''. In General, the gauge wires 0.014 '' x0.025 '' showed strength levels on the plateau of deactivation to 6 x smaller than 0.016 '' x0.022 '' caliber.

O conhecimento sobre as propriedades mecânicas dos fios de Níquel-Titânio (NiTi) termoativados das marcas mais acessíveis do mercado nacional ainda é limitado. Diante disso, o objetivo deste estudo foi avaliar e comparar por meio de testes de deflexão em 03 braquetes, os fios NiTi termo ativados retangulares de calibre 0,014’’x0,025’’ e 0,016”x0,022” de diferentes marcas (MORELLI® ORMCO®, ORTHOSOURCE®, ORTHOMETRIC®, EURODONTO® e ADITEK®). Todos os testes foram realizados na máquina de ensaio universal EMIC DL 2000 sob condições idênticas e controladas a uma temperatura de 36°C ± 0,5°C. Cinco medições (N=5) foram realizadas para cada espessura/marca de fio que foi deflexionado até um limite de 4,0mm a uma velocidade de 1,0mm/min. A cada 0,2mm (ida e volta) de deflexão a força correspondente foi aferida para a construção do gráfico de força x deflexão no programa Tesc versão 3.04. Cada gráfico foi avaliado individualmente segundo as seguintes variáveis: início da transformação martensítica (cN e mm), força máxima (cN), inicio e final do platô de desativação (cN e mm) e comprimento do platô (mm). As médias e o desvio padrão foram calculados para todas as variáveis e a análise estatística foi feita pelos testes ANOVA 2 critérios e Turkey ou Kruskal-Wallis e Dunn, a um nível de significância de 5%. Os resultados evidenciaram que nos testes dos fios 0,014’’x0,025’’ as marcas ORTHOMETRIC® e ORMCO® apresentaram os melhores resultados, assim como os fios das marcas MORELLI® e ORTHOSOURCE® para os fios 0,016’’x0,022’’. De uma forma geral, os fios de calibre 0,014’’x0,025’’ apresentaram níveis de força no platô de desativação até 6 x menores que os de calibre 0,016’’x0,022’’.
Comparison of the load/deflection ratio between the heat-activated ni-ti orthodontic wires 0.014''x0.025'' and 0.016''x0.022''
Keywords: Orthodontics; Orthodontic wires; Physical properties